The Role of Status Differentials and Homophily in the Formation of Social Support Networks of a Voluntary Organization. (March 2019) - Lee, Sun Kyong; Kim, Heewon; Piercy, Cameron W.
Given the important implications of social support on managing volunteers and their organizational commitment, we investigated how members of a Korean immigrant church ( N = 178) exchanged two distinctive kinds of social support (i.e., informational and tangible). We used theories of centrality and homophily to hypothesize patterns of social connections among organizational members. Employing exponential random graph modeling (ERGM), the current study estimated the likelihood of age and gender homophily/heterophily in forming supportive ties while considering structural parameters. The results of analysis of variance showed that members with higher socioeconomic status and in official staff positions in the church were more central in the informational support exchange. However, ERGM for both types of support networks did not show hypothesized gender and age homophily/heterophily of Korean immigrants' support exchange, suggesting the importance of other potential organizational and cultural influences. The findings shed light on the internal structuring of organizational support networks and suggest practical implications for managing organizational volunteers.